2018
DOI: 10.1097/pts.0000000000000492
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Early Warning Systems’ Effects on Nurses’ Clinical Performance and Adverse Events Among Deteriorating Ward Patients

Abstract: Objective Early warning systems (EWSs) are an integral part of processes that aim to improve the early identification and management of deteriorating patients in general wards. However, the widespread implementation of these systems has not generated robust data regarding nurses’ clinical performance and patients’ adverse events. This review aimed to determine the ability of EWSs to improve nurses’ clinical performance and prevent adverse events among deteriorating ward patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 23 publications
1
27
0
1
Order By: Relevance
“…These results were anticipated and in accordance with the training we supplied but somewhat contradictory when compared with previous research. In two recent systematic reviews concerning the effect of Early Warning Scores on the clinical performance of nurses, the authors concluded that the recording of vital signs improved after implementing EWSs (Lee et al, ; Saab et al., ). In most studies, an increase in the number of vital signs registered per observation was found which corresponded with our results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results were anticipated and in accordance with the training we supplied but somewhat contradictory when compared with previous research. In two recent systematic reviews concerning the effect of Early Warning Scores on the clinical performance of nurses, the authors concluded that the recording of vital signs improved after implementing EWSs (Lee et al, ; Saab et al., ). In most studies, an increase in the number of vital signs registered per observation was found which corresponded with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Only four studies investigated the effect of an RRS on nurses’ clinical performance in vital sign registration of which three had a before and after design (Kyriacos, Jelsma, James, & Jordan, ; Meester, Haegdorens, et al, ; Mitchell et al, ; Paterson et al, ). Although these studies suggest a positive impact on the quality of the registration of vital signs, they had small sample sizes or were of limited methodological quality (Lee, Kim, Kim, & Oh, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has shown that early warning scoring systems, such as the Modified Early Warning Score (MEWS) and the National Early Warning Score (NEWS), had good predictive abilities for in-hospital mortality and cardiac arrest (Royal College of Physicians, 2012; Smith, Prytherrch, Meredith, Shmidt, & Featherstone, 2013;Smith et al, 2014). In addition, although some studies have shown that the impacts of early warning scoring systems on patient outcome were unclear or there existed low-level evidence (Alam et al, 2014; Le Lagadec & Dwyer, 2017;Smith et al, 2014), the implementation of the systems tended to have positive outcomes (Downey, Tahir, Randell, Brown, & Jayne, 2017;Lee, Kim, Kim, & Oh, 2018). However, since the efficacy of such systems depends on patient populations and care settings (Le Lagadec & Dwyer, 2017;Wheeler et al, 2013), their performance with various patients in different settings need to be explored.…”
Section: Introductionmentioning
confidence: 99%